Herbert ('Red Pony') Ranch
Photo of the Herbert ('Red Pony') Ranch tour, led by Doctor Susan Shillinglaw (not pictured). Photograph was possibly taken on same day as the tour of Steinbeck's home in Salinas, Ca., and Pacific Biological Laboratory in Monterey, Ca. The old Herbert Ranch, 724 acres of land near King City, Ca., is now protected because of its location in the Pacific Flyway. The Pacific Flyway is a major north-south flyway for migratory birds in America, extending from Alaska to Patagonia, a sparsely populated region located at the southern end of South America. Negative and digital copy only. No hard copy.